NOTION OF INTERNATIONAL FINANCIAL LAW: SPECIFIC ISSUES - I. M. Lifshits (Московский журнал международного права, 2018)
Introduction. Diversity of international financial legal order results in different approaches to the term ‘international financial law’ (IFL). Author argues that the latter refers to the segment of international public law and governs relations between states and international intergovernmental organizations (IGOs).Materials and methods. The materials for the article were the works of  Russian and foreign researchers in the field of international economic and international financial law. . The methodological basis of the research consists of general scientific and special methods:  dialectical method, methods of analysis and synthesis, deduction and induction, comparative legal and historical legal methods.Research results. In the article the definition of the IFL is specified as well as its components. The subject matter of the IFL can be divided into three units: 1) public actors relations on the intercourse of money and securities and on the debt restructuring; 2) state relations on the internal regulation in financial affairs including public law regimes in budget, tax, currency control politics, banking, insurance and securities regulation and money laundry prevention as well as regulation of financial reporting, audit and appraisal activities; 3) relations of states and IGOs on the normative and institutional foundations of the international legal order.Discussion and conclusions. The author shows that the system of the IFL sources contains few multilateral international conventions. In particular cases variety of non-normative treaties (for instance loan agreements between the IMF and borrowing states or debt restructuring agreements in the framework of the Paris club) by applying the same or similar provisions forms a repeated practice of the states and IGOs. This practice being summarized in the documents of the international organizations and paraorganizations tends to form an international customs. Non-obligatory acts named ‘International Financial Standards’ (IFS) are widely used for the sake of harmonization of the different states laws. Standard setters of such IFSs are IGOs (IMF, IBRD, OECD), non-state organizations (International Accountant Standard Board) and bodies with intermediate character (Financial Stability Board, International Organization of Securities Commissions).